Phenomenological characterization and effect of reaction rate of coaxial reaction flow - LI Yu; FAN Yihui; BIAN Pingyan; ZHANG Haiguang; QU Haijun; WANG Jianping (河南理工大学学报. 自然科学版)
ObjectivesFor precise control of the coaxial reaction flow process， the macroscopic phenomenological characterization method and control law of reaction rate，Methodsthe cross-linking process of calcium alginate hydrogel hollow fiber was observed online by tracing Ca2+ with murexide indicator. The gray threshold of the crosslinking boundary was calibrated by the elution method. The average reaction rate of the coaxial reaction flow was defined from a macroscopic phenomenological perspective. The reaction rate value was calculated through the cross-linked layer thickness data extracted by online monitoring. The effects of the flow rate（constant flow rate ratio），concentration and co-flow distance of sodium alginate and calcium chloride solution on the thickness of cross-linked layer and average reaction rate were studied experimentally.ResultsThe results showed that： Compared with the hollow fiber size detected by online image recognition and elution method，the error between the two was only 1.09%， which could satisfy the engineering application requirements. With the increase of reactant concentration， the average reaction rate and cross-linked layer thickness were increased， and the calcium chloride concentration had a better regulation performance. Under constant flow rate ratio conditions， the cross-linked layer thickness decreased while the average reaction rate increased as the flow rate of the two solutions increased. As the co-flow distance of the reaction flow increased， the cross-linked layer thickness increased， and the average reaction rate gradully decreased. The above trends of the phenomenological average reaction rate affected by the fluid velocity field and the concentration of chemical reactants， which was consistent with the classical reaction rate indicating the validity of the phenomenological definition.ConclusionsThe online monitoring method of coaxial reaction flow， the phenomenological characterization method of reaction rate， and the influence law of material process parameters provided in this study， could help to realize the accurate control of hollow fiber’s structure size， cross-linked layer thickness and retained sol layer thickness， which could be helpful to promote and apply the coaxial reaction flow process.